La Innovación en la Organización de Servicios con el Sistema de Solidaridad en Perú - Arroyo Laguna, Juan (2012)
To analyze the performance of Solidarity System (SISOL) in Lima Metropolitan in the period 2004-2011, and its relation to its organizational model, in contrast to other performances and offer models existing in the health sector in Peru. The measurement of the performance indicators was based on data from SISOL, a survey to 4.570 users of SISOL applied in the last quarter of 2011, the National Household Surveys of the years 2003-2011 and statistical information from the Ministry of Health and Social Security. The study revealed positive results in terms of growth of SISOL´s demand in Lima, high productivity of consultations by human resource and high levels of user satisfaction. The study explains the relationship of these results with the characteristics of SISOL model: 1) the presence of specialists in primary care, 2) financial self-sustainability of the system, and 3) shared risk between public sector and micro-enterprise services. The strategy of development of this innovation was from outside of institutional contexts resistant to change. The results support the necessity of renewing primary health care, particularly for urban areas, correcting the unnecessary escalation. They also show the possibility of public-private synergy in a different model from outsourcing, in which both sectors share risks and act collaboratively in each facility. Finally, SISOL calls to imagine new articulation ways in segmented models.